Effect of Zn and P Levels on the Concentration and Uptake of N and N/Zn Ratio in Rainfed Pearl Millet (Pennisetum Typhoides S&H) - Aggarwal, R K; Singh, Panjab (Annals of Arid Zone, 2016)
Field studies on the effect of soil applied Zn (0, 15, 30 kg commercial ZnSO4/ha) and P (0.30,60,90 kg P205/ha) on N concentration and uptake, and N/Zn ratio in pearl millet revealed that the concentration and total N uptake increased with the increase in levels of Zn and P, but decreased when higher levels of one element when combined with low level of another. Drought during crop growth increased the concentration and decreased total uptake. N/Zn ratio in grain was 2-3 times higher than either in straw or root. Decrease in N/Zn ratio negatively affected the quality and production of grain.